PERANAN TEKNOLOGI PEMANTAUAN SECARA ONLINE DALAM PENGELOLAAN KUALITAS LINGKUNGAN - Wahjono, Heru Dwi; Yudo, Satmoko (Center for Environmental Technology, 2006)
In global industrial era, more than 70% industrial growth especially in Java will centrally around urban region. This matter can increase the environmental pollution as long as the progress of industry and technology development. Central and regional governments have continued to cope with the environmental pollution problem, although many environmental cases difficult to be resolved. This matter caused by the limited ability of observation technology and monitoring which conducted by the relevant institution and also because of the limited existing fund which allocated for the environment management. To increase the ability of environmental quality observation and monitoring technology in this time, we need the role of information and computation technology which can be used to observe and monitor online the source of pollution that resulting the environmental damages. To support this article we used the data of the case of information technology usage by the environmental institution in Japan. Ã‚Â Katakunci : Online monitoring, pengelolaan Llngkungan perairan, teknologi Informasi dan komputasi, sensor kualitas air.Ã‚Â